Molecular analysis of spinal muscular atrophy and modification of the phenotype by SMN2 - Mailman, Matthew D.; Heinz, John W.; Papp, Audrey C.; Snyder, Pamela J.; Sedra, Mary S.; Wirth, Brunhilde; Burghes, Arthur H.M.; Prior, Thomas W. (Genetics in medicine, 2002)
Purpose: This study describes SMN1 deletion frequency, carrier studies, and the effect of the modifying SMN2 gene on the spinal muscular atrophy (SMA) phenotype. A novel allele-specific intragenic mutation panel increases the sensitivity of SMN1 testing. Methods: From 1995 to 2001, 610 patients were tested for SMN1 deletions and 399 relatives of probands have been tested for carrier status. SMN2 copy number was compared between 52 type I and 90 type III patients, and between type I and type III patients with chimeric SMN genes. A fluorescent allele-specific polymerase chain reaction (PCR) -based strategy detected intragenic mutations in potential compound heterozygotes and was used on 366 patients. Results: Less than half of the patients tested were homozygously deleted for SMN1. A PCR-based panel detected the seven most common intragenic mutations. SMN2 copy number was significantly different between mild and severely affected patients. Conclusions: SMN1 molecular testing is essential for the diagnosis of SMA and allows for accurate carrier testing. Screening for intragenic mutations in SMN1 increases the sensitivity of diagnostic testing. Finally, SMN2 copy number is conclusively shown to ameliorate the phenotype and provide valuable prognostic information.